2009
DOI: 10.1016/j.marmicro.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The response of calcareous nannofossil assemblages to the Paleocene Eocene Thermal Maximum at the Walvis Ridge in the South Atlantic

Abstract: Compositions and abundances of calcareous nannofossil taxa have been determined in a ca 170 kyrs long time interval across the Paleocene/Eocene boundary at 1-cm to 10-cm resolution from two ODP Sites (1262, 1263) drilled along the flank of the Walvis Ridge in the South Atlantic. The results are compared to published data from ODP Site 690 in the Weddell Sea. The assemblages underwent rapid evolution over a 74 kyrs period, indicating stressed, unstable and/or extreme photic zone environments during the PETM hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 43 publications
3
57
0
Order By: Relevance
“…For instance, an increase in abundance of Discoaster and Fasciculithus was reported for some of the PETM section studied (e.g., Bralower, 2002;Tremolada and Bralower, 2004;Raffi et al, 2009), but these assemblage variations were not observed in other sections (e.g., Gibbs et al, 2006;Agnini et al, 2007a;Self-Trail et al, 2012). The only global calcareous nannofossil assemblage features of the PETM are represented by the evolutionary appearance of Rhomboaster/Tribrachiatus lineage, the presence during the CIE of short-lived species such as Discoaster araneus, and the disappearance of several species of fasciculiths Agnini et al, 2007a).…”
Section: Calcareous Nannofossil Assemblages Within the Context Of Cormentioning
confidence: 95%
“…For instance, an increase in abundance of Discoaster and Fasciculithus was reported for some of the PETM section studied (e.g., Bralower, 2002;Tremolada and Bralower, 2004;Raffi et al, 2009), but these assemblage variations were not observed in other sections (e.g., Gibbs et al, 2006;Agnini et al, 2007a;Self-Trail et al, 2012). The only global calcareous nannofossil assemblage features of the PETM are represented by the evolutionary appearance of Rhomboaster/Tribrachiatus lineage, the presence during the CIE of short-lived species such as Discoaster araneus, and the disappearance of several species of fasciculiths Agnini et al, 2007a).…”
Section: Calcareous Nannofossil Assemblages Within the Context Of Cormentioning
confidence: 95%
“…The standard calcareous nannofossil zonations of Martini (1971) and Okada and Bukry (1980) are widely used for low-and middle-latitude Eocene-Oligocene (E-O) biostratigraphic studies, and were used in this paper. To infer probable temperature and trophic variations of surface waters, most calcareous nannofossils were, when possible, allocated into groups of environmental affinities, largely following Haq and Lohmann (1976), Aubry (1992), Gardin and Monechi (1998), Bralower (2002a,b), Tremolada and Bralower (2004), Persico and Villa (2004), Gibbs et al (2006), Villa et al (2008), Raffi et al (2009) and Agnini et al (2011). Based on this literature, the following environmental groups were used: eutrophic taxa (Dictyococcites bisectus, Dictyococcites scrippsae, Reticulofenestra daviesii), and oligotrophic taxa (Cribrocentrum reticulatum, Ericsonia spp., Sphenolithus spp., Zygrhablithus bijugatus) (Appendix B).…”
Section: Methodsmentioning
confidence: 99%
“…documented at a number of locations [58,59]. Unfortunately, attempts to locate deep-sea sections that were positioned just below the CCD prior to the PETM, and thus might have recorded the transient overshoot, have yet to be successful.…”
Section: Massive Carbon Releasementioning
confidence: 99%